2019
DOI: 10.1155/2019/9792369
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Cartilage Graft of IGF1-Transduced Adipose Mesenchymal Stem Cells Embedded in an Alginate/Bovine Cartilage Matrix Tridimensional Scaffold

Abstract: Articular cartilage injuries remain as a therapeutic challenge due to the limited regeneration potential of this tissue. Cartilage engineering grafts combining chondrogenic cells, scaffold materials, and microenvironmental factors are emerging as promissory alternatives. The design of an adequate scaffold resembling the physicochemical features of natural cartilage and able to support chondrogenesis in the implants is a crucial topic to solve. This study reports the development of an implant constructed with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…To overcome mechanical tissue demands, a strategy used by our group [16] and others has been to incorporate decellularized ECM processed in the form of micronized particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome mechanical tissue demands, a strategy used by our group [16] and others has been to incorporate decellularized ECM processed in the form of micronized particles.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, biofunctionalization with an ECM derived from several tissues and decellularized organs has become more attractive and is used for the regeneration of tissues, such as skeletal muscle [12], blood vessels [13], nerves [14], and cartilage [15,16]. The ECM provides informative signals and a unique composition that mimics the natural tissue environment and leads to proper tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…To isolate Ad-MSCs, a modified version of the isolation protocol described in Moncada-Saucedo et al ( 19 ) was followed ( 20 ). To achieve this, lipoaspirate was centrifuged for 10 min at 1,000 x g in a 4˚C refrigerated centrifuge (5804R; Eppendorf), the aqueous phase was discarded and the adipose tissue was washed with PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…IGF-1 has been reported showing high anabolic effects and decrease in catabolic responses in articular cartilage metabolism in vitro [167,168]. Other studies have reported using different growth factors which were successful in producing several features that resembled typical articular cartilage [169][170][171]. Despite the capacity to promote cartilage matrix formation, growth factors have shown some drawbacks with IGF-1 associated with a loss of chondrocyte phenotype and extracellular matrix breakdown [168].…”
Section: Biochemical and Biomechanical Stimulationmentioning
confidence: 99%
“…Despite the capacity to promote cartilage matrix formation, growth factors have shown some drawbacks with IGF-1 associated with a loss of chondrocyte phenotype and extracellular matrix breakdown [168]. Furthermore, IGF-1 in human MSCs inhibited collagen II expression and overexpression can induce hypertrophic differentiation and mineralisation [172].…”
Section: Biochemical and Biomechanical Stimulationmentioning
confidence: 99%